Hepatitis-B-associated glomerular disease : a clinicopathological study of Hepatitis B virus associated Membranous Glomerulonephritis in Namibian and South African children 1974 – 2005 and a comparison with hepatitis B associated Membranous Glomerulonephritis as well as Idiopathic Membranous Glomerulonephritis in adults - Bates, William D. (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD (Med))--Stellenbosch University, 2011.